QCLab: a framework for query compilation on modern hardware platforms - Funke, Henning (Technische Universität Dortmund, 2022)
As modern in-memory database systems achieve higher and higher processing speeds, the performance of memory becomes an increasingly limiting factor. Although there has been significant progress, the bottleneck only has shifted. While earlier systems were optimized for memory latencies, current systems are rather affected by the limited memory bandwidth. Query compilation is a proven technique to address bandwidth limitations. It translates queries via Just-In-Time compilation to native programs for the target hardware. The compiled queries execute with very high efficiency and only with a bare minimum of communication via memory. Despite these important improvements, the benefit of query compilation in certain scenarios is limited. On the one hand query compilers typically use standard compiler technology with relatively long compilation times. Therefore the overall execution time can be prolonged by the additional compilation time. On the other hand, not all emerging database technology is compatible with the approach. Query compilation uses a tuple-at-a-time processing style that departs from the column-at-a-time or vector-at- a-time approaches that in-memory systems typically use. Especially data-parallel processing techniques, e.g. SIMD or coprocessing-techniques, are challenging to use in combination with the approach. This work presents QCLab, a framework for query compilation on modern hardware platforms. The framework contains several new query compilation techniques that allow us to address the mentioned shortcomings and ultimately to extend the benefit of query compilation to new workloads and platforms. The techniques cover three aspects: compilation, communication, and processing. Together they serve as basis for building highly efficient query compilers. The techniques make efficient use of communication channels and of the large processing capacities of modern systems. They were designed for practical use and enable efficient processing, even when workload characteristics are challenging.
Keywords: Query compilation; Modern hardware; Parallel data processing; 004; Abfragesprache; Parallelverarbeitung